Financial Distress in Textile and Garment Firms: The Role of Executive Compensation, Sales Growth, and Operating Capacity - Haifa Khairatun Hisan; Dudi Pratomo; Novy Fajriati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the relationship between financial difficulty and operating capacity, sales growth, and executive compensation in textile and apparel companies listed on the Indonesia Stock Exchange (IDX) between 2020 - 2024. Grounded in Signaling Theory, the study investigates whether these factors influence the likelihood of financial distress. Quantitative secondary data was utilized from yearly reports and financial statements. Purposive sampling was used to pick 17 companies for the sample, yielding 85 panel observations. The Altman Z-Score was used to gauge financial distress, and panel regression using the REM, which was chosen using the Chow, Hausman, and Lagrange Multiplier tests, was used to analyze the data. Higher compensation may improve managerial effectiveness and lessen financial challenges, based on the research, financial turmoil is significantly impacted negatively by executive salary. Sales Growth shows an insignificant effect, suggesting that increased sales do not necessarily improve a firm’s financial condition. On the other hand, operating capacity has a positive effect on financial distress, indicating that operational stress rather than better financial performance may be the cause of increasing asset turnover. Collectively, the independent variables significantly affect Financial Distress. These findings support Signaling Theory by demonstrating that managerial, growth, and operational factors provide signals regarding a firm’s financial condition. The results suggest that companies should implement effective executive compensation policies and improve operational management to mitigate financial distress risk. Future research is urged to include more variables and cover a wider range of industries in order to provide a more thorough knowledge of the factors that contribute to financial distress. Keywords: Executive Compensation, Financial Distress, Operating Capacity, Sales Growth, Signaling Theory